1992
DOI: 10.1520/jfs12002j
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Prevalence of Organic Brain Dysfunction in Maximum-Security Forensic Psychiatric Patients

Abstract: This is a descriptive study of 50 randomly selected male patients retained in a maximum-security state hospital for mentally disordered offenders. Data regarding the prevalence of several indicators of potential organic brain dysfunction are presented, including: (1) a diagnosis of any organic brain disorder, (2) a history of severe head injury with loss of consciousness, (3) a history of seizure activity, (4) evidence of cognitive impairment, (5) abnormal neurological findings, and (6) other relevant neurodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 29 publications
2
36
1
3
Order By: Relevance
“…The incidence of head injury with associated loss of consciousness at 31% was higher than expected than in a normal population (Whitman et al, 1984). An index of CNS impairment, as used by Martell (1992), that includes both the causes and consequences of CNS damage revealed that 58 (60%) of the population had at least one index and 27 had two or more. Martell (1992) reported one or more in 85% of his population and two or more in 64%, but Martell used a random sample that would have included patients with longer periods of hospitalization, which could have resulted in a sample with a higher frequency of neuropsychiatric impairment (Wint, 1993).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The incidence of head injury with associated loss of consciousness at 31% was higher than expected than in a normal population (Whitman et al, 1984). An index of CNS impairment, as used by Martell (1992), that includes both the causes and consequences of CNS damage revealed that 58 (60%) of the population had at least one index and 27 had two or more. Martell (1992) reported one or more in 85% of his population and two or more in 64%, but Martell used a random sample that would have included patients with longer periods of hospitalization, which could have resulted in a sample with a higher frequency of neuropsychiatric impairment (Wint, 1993).…”
Section: Discussionmentioning
confidence: 95%
“…In this investigation, comparable information on four of the five criteria used by Martell (1992) to investigate the prevalence of organic impairment in his study (head injury, seizure disorder, cognitive impairment and organic DSM-III-R diagnosis) was available. There were 58 (out of 96, 60%) who satisfied at least one out of these four criteria, 27 (28%) who satisfied two, and 4 (4%) who satisfied three.…”
Section: Interactionsmentioning
confidence: 99%
“…Si ce diagnostic a déjà été associé à la violence [61] ou à la récidive [14], il semblerait que la chronologie n'est pas simple. Il se pourrait que le développement d'un trouble organique mène au comportement déviant chez des personnes qui n'avaient pas de troubles du comportement (social) avant la maladie, mais également que la maladie se développe chez des sujets déjà …”
Section: Une Typologie En Lien Avec Les Autres Facteurs Identifiésunclassified
“…J. B. could benefit from the increasing acknowledgement in forensic practice of brain dysfunction (Marteli, 1992) and the need to recognise interactive patterns between biological and psychosocial factors (Volarka et al, 1992).…”
Section: Service Deliverymentioning
confidence: 99%